2017
DOI: 10.1039/c7ra07198a
|View full text |Cite
|
Sign up to set email alerts
|

UV/ozone-assisted tribochemistry-induced nanofabrication on Si(100) surfaces

Abstract: UV/ozone oxidation provides a simple and efficient method to prepare super-hydrophilic SiOx films for tribochemistry-induced nanofabrication on Si substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…This indicates that o DMS covers the top surface of the thin film due to its lower surface free energy. After RIE, the WCA of the Glc 1 - b -DMS n - b -Glc 1 thin film was determined to be 83.9°, which was in close agreement with that of SiO 2 (87.5°) [ 63 ]. These findings indicated that the saccharide domain was removed selectively and the o DMS segment was converted to SiO 2 .…”
Section: Resultsmentioning
confidence: 66%
“…This indicates that o DMS covers the top surface of the thin film due to its lower surface free energy. After RIE, the WCA of the Glc 1 - b -DMS n - b -Glc 1 thin film was determined to be 83.9°, which was in close agreement with that of SiO 2 (87.5°) [ 63 ]. These findings indicated that the saccharide domain was removed selectively and the o DMS segment was converted to SiO 2 .…”
Section: Resultsmentioning
confidence: 66%
“…Although it was not fully clear, the increase of the roughness with the treatment time could be partly attributed to further oxidation and photocorrosion of glass surface when it occurred more than 10 min [23]. It has been reported that hydrophilic hydroxyl groups can be generated on substrate surface during UVO treatment, which lead to the reduction of water contact angle of substrate surface [11,24]. On the other hand, the water contact angles of glass decreased drastically from 54 • to 9 • with the UVO treatment from 0 to 10 min, and then the contact angles continued to decrease (Figure 1).…”
Section: Pretreatment With Uv/ozone Exposurementioning
confidence: 95%
“…The mechanism of UVO-assisted rapid formation of high-quality PFDS SAM on glass surface is shown in Figure 4. The photo-oxidation reaction of UVO treatment is indispensable for rapid formation of high-quality PFDS SAM on a glass surface [11]. As illustrated in Figure 4a, the photo-oxidation reaction of UVO treatment can be summarized as surface contaminant decomposition and surface hydroxylation.…”
Section: Uv/ozone-assisted Rapid Formation Of Pfds Sammentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al [76] developed a UV/ozone-assisted tribochemistry-induced selective etching approach for the fabrication on silicon surface. UV/ozone system was used for the preparation of SiO x film on surface, and the oxidation film was demonstrated to be more beneficial for subsequent fabrication in contrast with dry, chemical, and thermal plasma-assisted oxidation.…”
Section: Tribochemistry-induced Selective Etchingmentioning
confidence: 99%